프로토타이핑 디자인 방법 연구 - 애플과 다이슨의 제품 개발 사례를 중심으로 - 김남희; Nam-hee Kim; 한승연; Seung-yeon Han; 정주영; Joo-young Jung (한국디자인포럼, 2024)
연구배경 제품의 물리적 요소들이 스크린상의 그래픽인터페이스로 대체되고, 기술의 발전으로 제품의 형태가 점차 단순화되고 있다. 이로 인해 물리적 요소의 적절한 적용과 제품의 특성이 고려된 최적화된 형태가 오히려 제품 차별화를 위해 중요한 요소로 강조되고 있다. 이에 이 연구에서는 애플과 다이슨의 성공적인 제품개발 사례를 통해 프로토타이핑 접근이 혁신적인 제품을 만드는데 현재에도 유효하게 기여하고 있으며, 최적화된 제품의 형태와 기능을 구성하는데 중요한 역할을 하고 있음을 살펴보고자 한다. 연구방법 연구는 프로토타이핑의 이론적 고찰로부터 시작하였고, 이론적 내용은 문헌 연구를 통해 진행하였다. 이후 애플과 다이슨의 제품 개발 사례 중 프로토타이핑 단계가 잘 나타나고 있는 사례를 문헌 연구를 통해 조사하였다. 이후 분석한 결과를 토대로 애플과 다이슨의 제품 개발 과정의 차이점을 분석하였다. 연구결과 애플과 다이슨은 제품 개발 과정에서 프로토타이핑 디자인 방법을 중요하게 다루고 있었다. 그러나 두 기업은 제품 개발의 방향성에 차이가 있음은 물론 이로 인해 프로토타이핑 방식에도 차이가 있었다. 애플은 디자인을 가장 중요한 요소로 여기는 반면, 다이슨은 기능을 중요하게 여겼고, 이러한 차이점은 프로토타이핑 진행 과정에 영향을 주고 있었다. 결론 애플과 다이슨의 사례를 통해 프로토타이핑 방법이 제품 개발에서 실제 어떻게 활용되고 있는지 살펴보았다. 프로토타입은 물리적인 형상을 통해 CAD 프로그램과는 다른 현장감을 제공한다. 또한 새로운 아이디어를 도출하고 문제 해결에 중요한 단서를 제공하는 프로토타이핑은 현재까지도 유효한 디자인 방법임을 확인할 수 있었다. Background As physical elements of products are gradually being replaced by graphical interfaces on screens and technological advancements simplify product forms, the emphasis on optimizing product shapes and applying appropriate physical elements has become crucial for product differentiation. This study aims to explore the role of prototyping, a key design methodology in configuring optimized product forms, through case studies of Apple and Dyson product development. Methods The research commences with a theoretical exploration of prototyping, with theoretical content derived from a literature review. Subsequently, case studies of Apple and Dyson product development, highlighting instances of the prototyping stage, were investigated through literature review. Based on the analyzed results, differences in the product development processes of Apple and Dyson were examined. Result Both Apple and Dyson placed significant importance on prototyping in their product development processes. However, differences in the direction of product development led to variations in the prototyping processes. While Apple prioritized design, Dyson emphasized functionality, resulting in distinctions in the execution of prototyping stages. Conclusion Through the examination of Apple and Dyson cases, the utilization of prototyping methodologies in product development was investigated. Prototypes offer a tangible representation, distinct from CAD programs, providing a sense of immediacy. Moreover, they remain a valid design method, offering the ability to generate new ideas and providing crucial clues for problem-solving in contemporary product development.